Peningkatan Kualitas Audit : Standar Auditing dan Sistem Pengendalian Mutu - H. Adilla Adha, Beby Marcha; Suryo, Medianto; Maulana, Dikdik (Jurnal SIKAP (Sistem Informasi, Keuangan, Auditing Dan Perpajakan), 2025)
Audit quality is possibilities when auditing a client's financial statements, violations can be found in the client's accounting system. An auditor is required to produce high-quality and good work, The purpose of this study is to determine partially and simultaneously the effect of the Implementation of Auditing Standards and Quality Control Systems on Audit Quality. This research method uses a quantitative approach. The data collection for this study used a questionnaire. The sample of this study was 65 Auditors working at a Public Accounting Firm in Bandung City, with a sample collection technique using probability simple sampling. The results of the analysis show that Auditing Standards have a significant effect on Audit Quality. The Quality Control System has a significant effect on Audit Quality. Auditing Standards and Quality Control Systems have a significant effect simultaneously on Audit Quality of 88.4%, while the remaining 11.6% is influenced by other unobserved variables.